Making rangelands more secure in Cameroon: Lessons learned and recommendations for policy makers, development actors and pastoralists - Azuhnwi, B.; Gidado, M.J.; Nsoh, M.F.; Ndamba, M.; Flintan, Fiona E. (2017)
In Cameroon, rangelands occupy about 20 % of surface area; provide critical habitat to many animal and plant species; offer many vital goods and services to society and are home to pastoralists, agropastoralists, crop farmers, fishermen and hunter-gatherers, who for centuries co-existed peacefully. In recent years this harmony is being threatened by changing land use patterns, poor land use planning and poor recognition of ownership rights. Despite efforts by state and non-state actors to improve pastoral tenure security little has been achieved because of poor coordination among actors and a complete absence of opportunities to document and or showcase these good initiatives. This study, supported by the ILC Rangelands Initiative, sought to identify, review and analyse the different initiatives that are contributing/have contributed in making rangelands more secure. A case study approach was used to document initiatives using primary and secondary sources and with choice predicated on the prominence, variety and indicated successes of the initiatives. Ten initiatives were showcased under five thematic areas ranging from: governance/decision making processes; resolving conflicts; land use planning; empowering communities; protecting pastoral resources. The results of this study will contribute to a more targeted development of future initiatives that build on past good practices.